Streptomyces isolate SOM013, a potential agent against microbial resistance and gastric ulcers - Kizito Eneye Bello; Ahmad Adebayo Irekeola; Ahmad A. Alshehri (Elsevier, 2024)
The menace of microbial resistance and re-emerging disease is still a problem for healthcare givers globally, and the need for newer sources of potent antibiotics has become paramount. This study investigated the antimicrobial and antiulcer activities of Streptomyces isolate SOM013. Streptomyces isolates were cultivated and purified following standard microbiological protocols. Secondary metabolites were recovered and characterized from Streptomyces isolate SOM013 via broth fermentation and extraction. Varying concentrations (0.5 mg/mL, 0.025 mg/mL and 0.0125 mg/mL) of the SOM013 extract were used for antimicrobial screening against resistant bacteria and medically important fungi (methicillin-resistant Escherichia coli, Oxacillin resistant Helicobacter pylori, Shigella spp, extended broad-spectrum resistant Pseudomonas aeruginosa, Streptococcus spp, Campylobacter spp, Candida albicans, Aspergillus niger, and Aspergillus flavus). The antiulcer activity of the SOM013 was also examined in a methanol-induced gastric ulcer animal model. A total of 23 Streptomyces spp were recovered from the study. Methanolic extract of the SOM013 isolates was more potent across the clinical test microorganisms compared to water extract. The antimicrobial activity was dose dependent, with methanolic extract at 0.05 g/mL displaying the highest zone of inhibition (18.8 ± 0.3 mm) when tested against extended broad-spectrum resistant Pseudomonas aeruginosa. Further, the extract's ulcer index and protection efficacy were significant as the concentration increased (P < 0.01). SOM013 isolate has a moderate antimicrobial and high antiulcer activity worthy of pharmacological exploration.